Differences in gait analysis and clinical outcome after TightRope or screw fixation in acute syndesmosis rupture: study protocol for a prospective randomized pilot study - Doll, Julian; Waizenegger, Stefan; Bruckner, Thomas; Schmidmaier, Gerhard; Wolf, Sebastian Immanuel; Fischer, Christian (Trials, 2020)
Ankle sprains and fractures are most common injuries in orthopedic and trauma surgery. The concurrent occurrence of syndesmosis ruptures in these injuries represents a more complex problem, as they often remain undetected. A proper and accurate treatment of injuries of the syndesmosis, both isolated and combined with fractures, is necessary to avoid long-term consequences (chronic instability, cartilage damage, and post-traumatic osteoarthritis). The most popular treatment option is a static screw fixation and the newly developed dynamic TightRope® (Arthrex, Naples, FL, USA). The aim of this pilot study is to compare monitor ankle range of motion and maximum ankle power in gait as functional outcome parameters of instrumented gait analysis, as well as clinical and radiographic outcome for assessing the stabilization of acute syndesmosis rupture with either a static implant (a 3.5 mm metallic screw) or a dynamic device (TightRope®).
Gesehen am 06.08.2020